FACTORS INFLUENCING RESILIENCE TO CLIMATE VARIABILITY AMONG SMALLHOLDER LOWLAND RICE FARMING HOUSEHOLDS IN NORTHERN GHANA - Issaka, Y. B; Donkoh, S. A; Kranjac-Berisavljevic, G. (UDS International Journal of Development, 2023)
The ability of smallholder farmers to adapt to changing climatic conditions is crucial in achieving domestic and global food security. The study analysed the resilience of smallholder lowland rice farmers to climate variability and the factors influencing the resilience of smallholder rice systems in the Savelugu municipality of the northern region of Ghana. The data was obtained using a cross-sectional questionnaire administered to 241 households and focus group discussions. A multi-dimensional Climate resilience index (CRI) was calculated for household resilience and used to determine relevant factors influencing household resilience through multiple regression analysis. Overall household CRI averaged 0.49, with transformative capacity, a major contributor with an index of 0.69, while adaptive and absorptive capacities were 0.45 and 0.33, respectively. The resilience analysis shows that income and food access, regular access to health, reliable access to improved water, agroecological conditions, resource governance and access to basic services are essential to household resilience against climate variability. The regression analysis results suggest that farmers’ age, cropping diversity, households’ primary income, plot position, soil quality, flooding, market access and FBO membership influence household resilience to climate variability. To be effective, policies to improve smallholder farmer resilience to climate variability must include diverse strategies allowing farmers the flexibility of selecting a combination of strategies that suits their socioeconomic and contextual situations; depart from farm-specific and technology-centric interventions to include other value chain dimensions and must address the climatic and non-climatic stressors confronting farmers concurrently to achieve the desired impact. Keywords: Climate Change and Variability, Rice, Resilience, Smallholder Agriculture, Ghana